Asuhan Kebidanan Komprehensif pada Ny. F, 25 Tahun, G2P1A0 dengan KEK di Puskesmas Bantarkawung, Brebes, 2024 - Nurlela Purnamasari; Endang Susilowati; Mupliha Mupliha (Jurnal Medika Nusantara, 2025)
Background: The maternal mortality rate in Brebes district in 2023 will again be the highest in Central Java after experiencing a decline in 2022. Objective: The aim of this research is to be able to implement Comprehensive Midwifery Care for Mrs F aged 25 years G2P1A0 with Chronic Energy Deficiency (KEK) at the Bantarkawung Community Health Center, Brebes Regency using Varney's seven-step midwifery management and SOAP documents. Research Method: The research method used is qualitative descriptive research with a case study approach. The case study carried out was in the form of comprehensive midwifery care that examined women during pregnancy, childbirth, newborns and neonates, the postpartum period and family planning using Varney's seven-step midwifery management and SOAP documents. Research Results: The results of comprehensive midwifery care for Mrs. F were that during pregnancy, KEK was found which was not resolved. Delivery by Sectio caesarea and newborn to normal neonate period. During the postpartum period, a problem was discovered in the form of hemorrhoids in the mother, then care was given in the form of advice to consume foods high in fiber and the problem was resolved. The mother uses contraception in the form of an implant. Conclusion: Based on this care, it was concluded that the care had been carried out in accordance with midwifery service standards and the problems found had been resolved.